Desempeño laboral de los trabajadores de la Hacienda Bananera “Santa María” del cantón Baba provincia de Los Ríos. - Vera Alvario, María Mercedes (2020)
The performance of the workers at present is one of the factors that the companies have more present at the moment of realizing any objective that involves efficiency and effectiveness. At the Hacienda Bananera Santa María, it does not have human resources planning that allows workers to feel more comfortable in an adequate work environment and with the necessary motivations to perform at their best. To develop this case study, a qualitative methodology was used to collect information in the analysis unit Hacienda Bananera Santa María. In the development of this work, the problems that arise in the hacienda are detailed and what actions have been taken before the investigation was carried out. The conclusions at the end of the work allow us to give a perspective of what all the problems found cause in the hacienda.